Ni alumina-based catalyst for sorption enhanced reforming - Effect of calcination temperature - Lj. Gavrilović; S.S. Kazi; A. Nelson; A.G.P. Oliveira; J. Meyer (Catalysis Communications, 2023)
Effect of calcination temperature (350 °C – 850 °C) on the physicochemical properties as well as catalytic performance of Ni-based catalyst for the hydrogen production via steam methane reforming (SMR) and sorption enhanced reforming (SER) has been investigated. Catalyst calcined at highest temperature (850 °C) shows formation of NiAl2O4 confirmed by XRD. Consequently, a much higher reduction temperature (875 °C) is required to reduce this Ni aluminate spinel to an active Ni catalyst. Catalyst calcined at highest temperature (850 °C) showed much higher CH4 conversion and H2 production in SMR compared to the catalysts calcined at lower temperatures. In addition, higher CH4 conversion and H2 production was observed for the 15%Ni/alumina_850 catalyst after aging (long exposure to steam and high temperature) compared to commercial reforming catalyst. Finally, a much better stability is observed for the 15%Ni/alumina_850 catalyst compared to the commercial reforming catalyst after 100 SER/regeneration cycles under relevant reaction conditions. The formation of NiAl2O4 during high temperature calcination plays a vital role in the robustness and stability of the Ni-based catalysts and can be useful synthesis procedure for increasing the catalyst lifetime.